Reformation of offenders in Nigerian correctional institutions - M., Hadi; Wan Mohamed, Wan Azlinda (Universiti Putra Malaysia Press, 2017)
This study examined the correlations between rehabilitation and reformation programmes such as moral instruction and counselling and medical services in Nigerian correctional institutions. A survey design was adopted. The participants were 224 offenders selected from seven correctional institutions in Nigeria. Questionnaire items were administered. Pearson correlation was used to examine the relationships between the variables. The findings reveal a moderate positive significant relationship between moral instruction and rehabilitation; there is a strong positive significant relationship between counselling services and rehabilitation and there is a strong positive relationship between medical care and rehabilitation. It is therefore recommended that Nigerian correctional institutions be in compliance with international best practice. More effort should also be given towards the teaching of moral instruction that has been identified as moderate because the higher the moral instruction given to offenders the higher the offender rehabilitation.